ASEAN-Japan Relations - Shiraishi, Takashi; Kojima, Takaaki (ISEAS, 2013)
"As we celebrate the 40th Anniversary of the ASEAN-Japan Dialogue Partnership, the essays in this book remind us, and amplify the ASEAN-Japan relations. The complexities of this relationship, including the external influences which have impinged on its development over the years, are cogently discussed and recorded for the younger generation and students of ASEAN-Japan ties. The intricacy and spread of ASEAN-Japan cooperation mechanisms are also well highlighted in this book, while several thought-provoking commentaries on the future of this four-decade old partnership give pause to the readers. Many of the challenges that exist in this relationship originated from domestic political dynamics in the ASEAN countries and Japan, as well as from the neighbouring states and key trading partners." Ambassador Ong Keng Yong, Former ASEAN Secretary General "The monograph on ASEAN-Japan relations is the intellectual highlight of the 40 years anniversary of ASEAN-Japan cooperation. ASEAN has become an indispensable partner and friend of Japan and its role as the hub of cooperation, development and stability in the region will without doubt become even more important after the establishment of the ASEAN Communities in 2015. The monograph containing contributions of the most renowned and respected experts on ASEAN provides us with enlightening overview, inspiration as well as guidance for our future common path. I would like to recommend this monograph to everybody interested in the further deepening of the ASEAN-Japan relations." Ambassador Yoshinori Katori, Ambassador of Japan to Indonesia, Former Ambassador in charge of ASEAN